THREE CEPHEIDS IN GALACTIC OPEN CLUSTERS: CHEMICAL COMPOSITION AND EVOLUTION - Usenko, I. A.; Kovtyukh, V. V. (Одеські астрономічні публікації, 2017)
Three classical Cepheids in galactic open clusters (CF Cas, DL Cas and WZ Sgr) were investigated, using high-resolution CCD spectra. Their Teff and EB-V estimations have a good agreement with photometrically determined ones. CF Cas and DL Cas have metallicity values, close to those of the Sun, whereas WZ Sgr has overabundant metallicity content with Z=0.029. Chemical abundance data show that they are the post first dredge-up stars. C and O content and ages have a good agreement with the theoretically predicted values. All these objects have a good fit with the PL relation for galactic Cepheids.